HUBUNGAN KEANEKARAGAMAN JENIS BURUNG DAN KOMPOSISI POHON DI KAMPUS 2 UIN WALISONGO SEMARANG - Mukhammad akmal surur; Muhammad A'tourrohman; Arifah Purnamaningrum (Jambura Edu Biosfer Journal, 2020)
Various species of birds can be used as bio-indicators of the environmental quality of an area. The diversity of tree species is directly proportional to the diversity of bird species. The purpose of this study was to determine the environmental quality of campus 2 Walisongo UIN Semarang through parameters related to the diversity of bird species with tree composition. This study uses a census method to collect tree composition data, and the number of counting points is used as a bird species data collection technique. The research sites are in four campus areas 2 of UIN Walisongo, namely: zone A in the Taman Fuhum area (east of the Faculty of Usuluddin and Humanities), zone B in the Faculty of Science and Technology area, zone C in the Unyil Park area of the Faculty of Tarbiyah and Teacher Training (FITK) and zone D in the North forest area of the Faculty of Science and Mathematics Technology. The results show zone D has the highest level of tree variation and bird species variation. Consists of 81 species of trees and 13 species of birds. In contrast zone, C has the lowest level of tree variation and lowest variation of bird species. The number of tree species is related to variations in the number of bird species. It can be concluded that the best environmental quality on campus 2 of UIN Walisongo is in zone D. The lack of diversity of bird and tree species in several areas on campus 2 of UIN Walisongo Semarang shows that there is a need for reforestation and tree planting to increase the diversity of bird species as parameters of environmental quality in campus 2 UIN Walisongo Semarang.